Variáveis locais e da paisagem influenciando a comunidade de formigas em áreas antropizadas em região de transição dos biomas Mata Atlântica-Cerrado - Silva, Olívia Carolina Tonussi da (2020)
Anthropic changes in land use modify the landscape and cause habitat loss and fragmentation. Fragmentation and monoculture favour the proliferation of some species and extinguish others. The composition and proportion of each land use within the matrix affect the population dynamics and these environment changes can be assessed using bioindicators, such as the ants. This work aimed to analyze how local and landscape variables influence the ant community in anthropized areas in a transition region of the Atlantic Forest-Cerrado biomes. Eight areas of native forest and eight areas of eucalyptus in buffers of up to 700m radius, and less than 300m apart, were used in this study. The ants were collected in a 180-meter-long transect per area. Each transect contained 10 pitfall traps for arboreal ants and 10 for epigenic ants, 20 meters apart. A sample of the local variables: litter and circumference of the base of trees was collected next to each trap. Percentage of landscape variables: pasture, native forest, eucalyptus, water, buildings, agriculture, and exposed soil were collected within six buffer sizes ranging from 200 to 700 m in radius, delimited from the central point of the transect utilizing satellite images. The native forest presented the greatest richness, with 77 species out of 89 collected. The sampled environments show differences in species composition. The local and landscape variables did not influence the richness, according to the variation in the size of the buffers, but did the composition. The exposed soil variable had a greater influence on the composition of ants. We conclude that the native forest is fundamental in the conservation of biodiversity. However, it is highly dependent on the composition and intensity of landscape use. Eucalyptus plantations affect the composition of ants, and cause decrease in species richness, but they have conservation value, contributing to the maintenance of services and preservation of species.